Evaluación de varios tipos de sustratos naturales en mezclas con abonos orgánicos en la reproducción de plántulas de Café Arábico (coffea arábiga) en la zona de Babahoyo - Álvarez Peña, Marcos Ubaldo (2014)
Coffee is one of the most important and cultivated crops, not only in Ecuador but of the world, for this reason it is of great economic and social importance. The UN estimates that is planted in over forty countries, being consumed by more than 50 % of the population in these places. In Ecuador it is estimated that approximately 300,000 ha are cultivated; mainly in the provinces of Guayas and Los Rios. Presents a national average yield of 350 kg/ha, which is considered low compared to other countries. The Los Rios province, produces coffee in about 62,000 ha, of which 70 % is not modernized. The objective of this research was to evaluate various types of media in the reproduction of Arabica coffee seedlings (Coffea arabica) in the Babahoyo. The research was conducted in the grounds of the Experimental Farm "San Pablo", Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7,5 of satellite Babahoyo-Montalvo. Red Caturra variety coffee was investigated with 10 treatments with various substrates in plots of 20 cases, which were distributed in a completely randomized design blocks. For the evaluation of the average Tukey test at 5 % probability was used. During the crop cycle were evaluated: plant height, leaf area, stem diameter, number of leaves per plant, root length.......